Newspaper Influence on Public Opinion Formation during Intra-Party Elections in Nigeria: A Discourse Analysis - Samuel George Jacobs (Darul Yasin Al Sys, 2026)
This study investigates the influence of newspaper discourse on public opinion formation during intra-party elections in Nigeria, with specific focus on the 2022 party primaries. Anchored in Framing Theory, the study examines how selected national newspapers shaped public perceptions of the credibility, transparency, and fairness of the primaries through their patterns of coverage. Library-based desk research and discourse analysis were employed to analyze newspaper content from seven national dailies: The Punch, The Guardian, Vanguard, ThisDay, Daily Trust, The Nation, and Leadership. Particular attention was given to language use, framing devices, and the representation of major political parties, including the APC, PDP, and LP. The findings reveal that the newspapers employed dominant frames such as conflict, power struggle, zoning debate, and internal democracy narratives, which influenced readers’ perceptions of electoral fairness. In some cases, newspaper reports amplified crises and irregularities within certain parties while downplaying similar issues in others. Similarities and differences were also observed in how the newspapers portrayed political parties, with some newspapers offering more critical scrutiny than others. Through the lens of Framing Theory, the study demonstrates how newspaper coverage can shape what the public considers important, credible, and politically significant during sensitive electoral periods such as party primaries. The study concludes that Nigerian newspapers play a significant role in shaping political discourse and public trust during intra-party elections. It recommends improved journalistic training on ethical framing, active media monitoring by regulatory bodies, and stronger collaboration between political parties and the media to foster balanced coverage, strengthen internal party democracy, and support Nigeria’s democratic development.